When integration backfires: exploring collaborative gamification in mathematics classroom - June Wei Yap; Victor Goh Weng Yew (Institute of Advanced Engineering and Science, 2026)
As the importance of mathematics literacy increased sharply in the era of artificial intelligence (AI), the present study developed a new teaching modality—collaborative gamification—to reduce mathematics anxiety and increase mathematics intrinsic motivation. A quasi-experimental, between-subject design using pre-existing classroom groups was employed to explore the effects of different teaching modalities on mathematics anxiety, mathematics intrinsic motivation, and mathematics achievement, and to examine whether the achievement outcomes could be mediated by these psychological factors. A total of 175 Malaysia Form 1 students were separated and exposed to different mathematics teaching modalities for one week. Results supported the effects of collaborative learning and gamification on psychological factors, which contributed to higher mathematics achievement. However, collaborative gamification neither reduced mathematics anxiety nor increased mathematics intrinsic motivation and was instead associated with lower mathematics achievement. These counterintuitive findings may be explained by the increased instructional complexity that result in cognitive overload, limiting students’ capacity for conceptual processing. The counterbalancing effect of elements may explain the non-significant improvement in psychological factors. These findings highlight the importance of careful instructional design, emphasizing the need to limit extraneous elements, align pedagogical features with learning objectives, and preserve sufficient time for concept development when implementing student-centered teaching modalities.